História em quadrinhos como estratégia para abordar DST/aids com adolescentes - Oliveira, Rodrigo Cena de [UNESP]; Lima Neto, José Luiz de [UNESP]; Almeida, Margareth Aparecida Santini de [UNESP]; Duarte, Marli Teresinha Cassamassimo [UNESP]; Alencar, Rúbia Aguiar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: It is observed a high vulnerability degree among teenagers, in either individual or social terms, related to sexual and reproductive health aspects, such as unplanned pregnancy and HIV infection. Concerned about this matter, teachers and students of Nursing, Medicine and Biomedicine work in two elementary schools in the city of Botucatu (SP), in Brazil since 2002, with young and adolescents through educational activities addressing STD / AIDS prevention and promotion of sexual and reproductive health. Experience description and relevance: This work consisted of pre-graduate students’ visits in the public schools, planned by the teachers involved in the project and participants of a university Academic League focused on discussions about STD / AIDS and their prevention. In this context, an educational booklet in the form of comics was developed which served as a basis for discussions with elementary school students about the vulnerability of young people. This comic book is designed to adolescents in sexual debut and was developed by university students committed to using a language owned by adolescents and weave a plot involving vulnerability contexts such as alcohol abuse, psychological pressure from the sexual partner and not using condoms. In order to approach the target audience, the story takes place in a common situation in the lives of young adolescents: The main character "Laura", a common teenager accompanied by her best friend, goes to a party at a friend's house. Then the protagonist finds the boy who she is interested in and together they have a sexual contact without condom, which results in the acquisition of an STD. After reading the story, the reasons that led the protagonist to expose herself were discussed, focusing on identifying vulnerable situations, addressing the risks of the actions taken by the characters. In addition, the comic book provides information about the STD acquired by the main character and questions that encourage the reader's reflection, which were discussed with the students, such as: "If I don’t drink with friends will I be a boring person?" and "What do you think of having sex without condom with someone you trust?". Comments: The work contributed to both public school students and pre-graduate students, through knowledge thickening and better critical reflection of this theme, providing a multidisciplinary work involvement, experience exchange and recognition of the importance in actions in the community.

Introdução: Observa-se entre adolescentes, um alto grau de vulnerabilidade, seja individual ou social, relacionada a aspectos da saúde sexual e reprodutiva, como a gravidez não planejada e a infecção pelo HIV. Preocupados com esta temática, docentes, graduandos de Enfermagem, Medicina e Biomedicina atuam em duas escola da rede pública de Botucatu desde 2002, com jovens e adolescentes, mediante ações educativas abordando questões de prevenção das DST/aids, e de promoção da saúde sexual e reprodutiva. Descrição da Experiência e relevância: Este trabalho consistiu em visitas dos universitários nas escolas, planejadas com os docentes envolvidos no projeto e universitários participantes de uma Liga Acadêmica voltada a discussão de DST/aids e sua prevenção. Neste contexto, desenvolveu-se uma cartilha educativa na forma de História em Quadrinhos que serviu como base para discussões com os alunos do ensino fundamental acerca da vulnerabilidade dos jovens. Esta História em Quadrinhos tem como alvo os adolescentes em início da vida sexual e foi desenvolvida por universitários jovens, empenhados em utilizar uma linguagem própria dos adolescentes e tecer um enredo que abordasse contextos de vulnerabilidade como o uso abusivo de bebidas alcoólicas, pressões por parte do parceiro sexual e o não uso de preservativo. Com o intuito de se aproximar do público alvo, a história ocorre em uma situação corriqueira na vida dos jovens: A personagem principal "Laura", uma adolescente comum, acompanhada de sua melhor amiga, vai a uma festa na casa de um amigo. Em seguida, a protagonista encontra o rapaz por quem tem interesse e juntos têm um contato sexual sem preservativo, que resulta na aquisição de uma DST. Ao fim da leitura, foram discutidas as razões que levaram a protagonista a se expor, com enfoque na identificação de situações de vulnerabilidade, abordando os riscos das ações adotadas pelas personagens. Além disso, a HQ traz informações a respeito da DST adquirida pela personagem e questões que suscitam a reflexão do leitor e que foram discutidas com os alunos, como: "Se eu não beber com os amigos eu serei careta?" e "O que você acha de transar sem camisinha com uma pessoa que você confia?". Comentários: O trabalho contribuiu, tanto para alunos da escola quanto para os universitários, para o aprofundando do conhecimento e a reflexão crítica dessa temática, possibilitando a vivência de trabalho multiprofissional, troca de experiências e reconhecimento da importância de ações na comunidade.
Keywords: Sexual and reproductive health; Prevention; Sexually transmitted diseases and AIDS; Saúde sexual e reprodutiva; Prevenção; Doenças sexualmente transmissíveis e aids